The Microetching Effect on the Shear Bond Strength of Orthodontic Metal Brackets - Hakam H Sabah (University of Mosul, College of Dentistry, 2011)
Aims: To evaluate and to compare the shear bond strength of new brackets, new microetched brackets and debond microetcher clean brackets when bond to virgin and previously bond teeth. Materials and methods: Thirty human premolars were randomly assigned into three groups, 10 teeth for each. Group V1 (virgin teeth bonded by new brackets), group V2 (virgin teeth bonded by new microeched brack-ets), and group V3 (virgin teeth bonded by debonded micretched cleaned brackets). All groups tested for shear bond strength. After that all teeth cleaned from composite and randomly assigned again into three groups, 10 teeth for each group. Group P1 (previously bonded teeth rebonded by new brackets), group P2 (previously bonded teeth rebonded by new microetched brackets), and group P3 (previously bonded teeth rebonded by debonded microetched clean brackets) and again all groups tested for shear bond strength. Results: There are no significant differences between virgin teeth groups and previously bonded teeth when clean previously bonded teeth from old adhesive as descried in this study however the previously bonded teeth groups showed the lower mean value than virgin teeth. New microetched and debonded micretched brackets groups showed significantly higher value in comparing with new bracket groups while there were no significant differences between new micretched and debonded mi-croetched groups with greater mean value for new micretched groups. Conclusion: Bracket recycled by microetching using 50-μm aluminum oxide particle was appears to be very effective method for bracket accidental debonded and Previously bonded teeth had shear bond strengths comparable to vir-gin teeth(new bonded) when adhesive remnant removed by